Mangrove Density Analysis Using Landsat 8 The Operational Land Imager (OLI) a Case Study Bengkulu City - Srifitriani, Abditama; Parwito, Parwito; Supriyono, Supriyono; Oktalia, Lola (Sumatra Journal of Disaster, Geography and Geography Education, 2020)
The change in crown density is an indication for monitoring its quality. The use of satellite imagery on remote sensing data in the form of Landsat has been carried out. Along with the development of the Landsat series satellite imagery, in this study, Landsat 8 OLI image processing was carried out on May 27, 2019, to analyze the distribution and density of mangroves using vegetation index analysis on the West Coast of Bengkulu City. The mangrove identification stages were carried out using the composite band RGB 564, then the mangrove and non-mangrove objects were separated using the unsupervised classification method. The next step is to analyze mangrove density using the NDVI formula. The results showed that the mangrove area on the West Coast of Bengkulu was 155.24 Ha. The analysis of the vegetation index in the mangrove area showed that dense density classes dominated the mangrove density conditions